2008
DOI: 10.5194/acp-8-7367-2008
|View full text |Cite
|
Sign up to set email alerts
|

Emission of sunscreen salicylic esters from desert vegetation and their contribution to aerosol formation

Abstract: Abstract. Biogenic volatile organic compounds (BVOC) produced by plants are known to have an important role in atmospheric chemistry. However, our knowledge of the range of BVOCs produced by different plant processes is still expanding, and there remain poorly understood categories of BVOCs. In this study, emissions of a novel class of BVOC emissions were investigated in a desert region. Our study considered 8 species of common desert plants: blackbrush (Coleogyne ramosissima), desert willow (Chilopsis lineari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Shim et al (2007) used inverse modeling to estimate global average biogenic emissions of hydrogen cyanide which is emitted from thousands of plant species, including many economically important food plants, when they are wounded. Matsunaga et al (2008) observed significant emissions of the "sunscreen" compounds, homosalate (C 16 H 22 O 3 ) and 2-ethylhexyl salicylate [also known as octyl salate] (C 15 H 22 O 3 ), from Mojave desert plants and much lower emissions from temperate forest tree species. They were the major BVOC emission observed from mesquite (Prosopis spp.)…”
Section: Model Parametersmentioning
confidence: 99%
“…Shim et al (2007) used inverse modeling to estimate global average biogenic emissions of hydrogen cyanide which is emitted from thousands of plant species, including many economically important food plants, when they are wounded. Matsunaga et al (2008) observed significant emissions of the "sunscreen" compounds, homosalate (C 16 H 22 O 3 ) and 2-ethylhexyl salicylate [also known as octyl salate] (C 15 H 22 O 3 ), from Mojave desert plants and much lower emissions from temperate forest tree species. They were the major BVOC emission observed from mesquite (Prosopis spp.)…”
Section: Model Parametersmentioning
confidence: 99%
“…Among polymers, physico-chemical properties for VOC system construction are generally suitable for rigid polymers with low amorphous phase (high crystalline phase) fraction such as fluorinated hydrocarbons -PFA (perfluoroalkoxy), FEP (fluorinated ethylene propylen), and PTFE brands (e.g. Teflon ® and Chemfluor ® ) (Geosyntec consultants Inc. For gas exchange enclosures (cuvettes), glass, although fragile, typically has very low adsorption capacity for most VOCs and therefore has been used in many sampling systems (Beauchamp et al, 2005;Copolovici et al, 2011;Copolovici and Niinemets, 2010;Fuentes et al, 1995;Hüve et al, 2007;Matsunaga et al, 2008;Papiez et al, 2009;Rasulov et al, 2009a;Wildt et al, 2003). Glass cuvettes without (Beauchamp et al, 2005;Copolovici et al, 2011;Hüve et al, 2007;Wildt et al, 2003) and with temperature control have been used (Fig.…”
Section: Materials Used In Gas-exchange Systemsmentioning
confidence: 99%
“…Glass cuvettes without (Beauchamp et al, 2005;Copolovici et al, 2011;Hüve et al, 2007;Wildt et al, 2003) and with temperature control have been used (Fig. 1a, b, Copolovici and Niinemets, 2010;Matsunaga et al, 2008;Papiez et al, 2009;Rasulov et al, 2009a). Cuvettes made of stainless steel with glass windows and polymer seals have also been found to have satisfactory terpenoid recovery, although memory effects leading to long equilibration times have been noted as a major disadvantage (Helmig et al, 2004).…”
Section: Materials Used In Gas-exchange Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salicylate esters display immunity against other organisms 1,2 in plants, regeneration effects 3 and possibly a protective effect against UV radiation in plants. 4 Synthetic salicylic acid derivatives are well known as biological active compounds such as analgesic and antifungal 5 and are also part of cosmetic formulations. 6 Some recent works refer to application of salicylic esters and salicylic acid-based dendrimers as potential drug carriers.…”
Section: Introductionmentioning
confidence: 99%